2006
DOI: 10.1037/0735-7044.120.1.201
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the disruptive effects of (+/-)3,4-methylene dioxymethamphetamine (MDMA) on delayed matching-to-sample performance in the rat.

Abstract: Recent evidence suggests that the disruptive effects of acute exposure to (+/-)3,4-methylene dioxymethamphetamine (MDMA) on memory performance may be the result of increased confusion between previous-trial and current-trial events. The current study tested this hypothesis by examining the effects of MDMA on performance of rats in a delayed matching-to-sample procedure when the length of the intertrial interval (ITI) was altered. Consistent with the possibility that limiting the conditions under which response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 25 publications
(47 reference statements)
4
28
0
Order By: Relevance
“…Indeed, accuracy of responding remained quite high across all doses of MDMA in both the OST and SD conditions. This account is consistent with previous findings from Harper (2005, 2006) that MDMA-induced errors can be attenuated by increasing the discriminability of relevant cues and more general findings that behavior under strong stimulus control is less sensitive to drug effects (Katz, 1982; 1983). Such an account is also consistent with more general notions about the role of task difficulty in its sensitivity to MDMA in human populations (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, accuracy of responding remained quite high across all doses of MDMA in both the OST and SD conditions. This account is consistent with previous findings from Harper (2005, 2006) that MDMA-induced errors can be attenuated by increasing the discriminability of relevant cues and more general findings that behavior under strong stimulus control is less sensitive to drug effects (Katz, 1982; 1983). Such an account is also consistent with more general notions about the role of task difficulty in its sensitivity to MDMA in human populations (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…The conclusions of the above studies were that acute MDMA results in working memory impairments. However, it has been argued that these findings do not involve working memory effects, but rather reflect disruptions of reference memory involving the rules or strategies associated with a given task (Harper et al, 2005; 2006; Kay et al, 2010). As an illustration, Kay et al (2010) used a version of the radial arm maze designed to separate working and reference memory and found that MDMA had no effect on the working memory task (arms were always baited for one visit), but impaired the reference memory task (arms that were never baited throughout the experiment).…”
Section: Discussionmentioning
confidence: 99%
“…Although delayed matching-to-position procedures are frequently used in rodent studies of working memory [39], we modified the task so that rats were required to press the rear-lever during the retention interval [40]. This rendered the task closer to the NIMH [36] definition of working memory, as rats had to actively maintain task relevant information while completing the rear-lever task that may interfere with this maintenance.…”
Section: Methodsmentioning
confidence: 99%